Familial hypercholesterolemia: case series of a rare condition - O. P. Ishevskaia; A. M. Namitokov; S. V. Kruchinova; E. D. Kosmacheva (Российский кардиологический журнал)
Introduction. Cardiovascular events at a young age are often the first manifestation of a genetic disorder such as familial hypercholesterolemia. High cholesterol levels, xanthomas and xanthelasmas, as well as a positive family history of cardiovascular disease, make it possible to identify a group of patients subject to genetic research. The identification of a specific mutation helps to determine further strategy not only for a patient, but also to his or her immediate relatives, thereby effectively conducting both secondary and primary prevention of atherosclerosis complications.Brief description. Using the example of patients from the Krasnodar Lipid Center, the relevance of genetic testing and cascade screening is demonstrated. We show problems of delayed diagnosis and low medical adherence, as well as the ways to optimize care for patients with genetic lipid metabolism disorders.Discussion. The rise in the incidence of cardiovascular events at a young age in developed countries prompts the search for more improved screening and diagnostic methods for familial hypercholesterolemia. The optimal age of initiation of lipid-lowering therapy in children with established familial hypercholesterolemia is also discussed. While secondary prevention appears to be clearer, there is still insufficient achievement of low-density lipoprotein cholesterol targets in patients with a previous cardiovascular event.